Martensitic Transformation and Metamagnetic Transition in Co-V-(Si, Al) Heusler Alloys - Kousuke Nakamura; Atsushi Miyake; Xiao Xu; Toshihiro Omori; Masashi Tokunaga; Ryosuke Kainuma (Metals, 2021)
This study investigates the crystal structure, martensitic transformation behavior, magnetic properties, and magnetic-field-induced reverse martensitic transformation of Co64V15(Si21–xAlx) alloys. It was found that by increasing the Al composition, the microstructure changes from the martensite phase to the parent phase. The crystal structures of the martensite and parent phases were determined as D022 and L21, respectively. Thermoanalysis and thermomagnetization measurements were used to determine the martensitic transformation and Curie temperatures. Both the ferromagnetic state of the parent phase and that of the martensite phase were observed. With the increasing Al contents, the martensitic transformation temperatures decrease, whereas the Curie temperatures of both the martensite and parent phases increase. The spontaneous magnetization and its composition dependence were also determined. The magnetic-field-induced reverse martensitic transformation of a Co64V15Si7Al14 alloy under pulsed high magnetic fields was observed. Moreover, using the results of the DSC measurements and the pulsed high magnetization measurements, the temperature dependence of the transformation entropy change of the Co-V-Si-Al alloys was estimated.